The Influence of Spirituality, Sciences, School Principal Leadership, Teacher, Link & Match Concept between the Educational and Bussiness on Education Quality and Sports Achievement - Salsabila Andrina; Ranti Karlaili (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
This research aims to investigate the interplay between spirituality, sciences, school principal leadership, teacher engagement, and the link & match concept between education and business, and their impact on education quality and sports achievement. The study employs a qualitative approach, utilizing purposive sampling to select participants. Data analysis involves thematic analysis to derive patterns, themes, and connections within the collected data. Preliminary findings suggest intricate relationships between the identified factors, indicating their significant influence on both education quality and sports achievement. This research contributes to understanding the multifaceted dynamics shaping educational outcomes and athletic success, offering insights for educational leaders, policymakers, and practitioners.